Does the way we read others' mind change over the lifespan? Insights from a massive web poll of cognitive skills from childhood to late adulthood. (January 2017) - Klindt, David; Devaine, Marie; Daunizeau, Jean
Abstract: Mentalizing or Theory of Mind (ToM), i.e., the ability to recognize what people think or feel, is a crucial component of human social intelligence. It has been recently proposed that ToM can be decomposed into automatic and controlled neurocognitive components, where only the latter engage executive functions (e.g., working memory, inhibitory control and task switching). Critical here is the notion that such dual processes are expected to follow different developmental dynamics. In this work, we provide novel experimental evidence for this notion. We report data gathered from about thirty thousand participants of a massive web poll of people's cognitive skills, which included ToM and executive functions. We show that although the maturation of executive functions occurs in synchrony (around 20 years of age), this is not the case for different mentalizing competences, which either mature before (for elementary ToM constituents) or after (for higher-level ToM). In addition, we show that inter-individual differences in executive functions predict variability in higher-level ToM skills from the onset of adulthood onwards, i.e., after the complete maturation of executive functions. Taken together, these results indicate that the relative contribution of ToM's controlled component significantly changes with age. In particular, this implies that, over the lifespan, people may rely upon distinct cognitive architectures when reading others' minds.